FIRST RECORD OF THE FRESHWATER CROAKER Plagioscion ternetzi BOULENGER 1895 (EUPERCARIA: SCIAENIDAE) IN THE QUEGUAY RIVER AND THE URUGUAY RIVER BASIN (Boletín de la Sociedad Zoológica del Uruguay, 2021)
In this study we report the first known record for the presence of the sciaenid species Plagioscion ternetzi in the Uruguay River Basin, at the specific location of the Queguay River, 20 km upstream from its mouth into the Lower Uruguay River. This finding extends the currently known distribution of the species in Uruguay (inner Río de la Plata Estuary) approximately 200 km northwards.
Keywords: Freshwater croaker; Sciaenidae; Fishes from the Queguay River; Fishes from Uruguay